Digest of Agricultural Statistics - Government of Oyo State of Nigeria (Ibadan, Nigeria : Ministry of Finance and Economic Development, 1977)
This is the maiden issue of the Oyo State of Nigeria "Digest of Agricultural Statistics". It is the main statistical publication on the State's Agricultural activities
osc 20/05/2019
Arch
Keywords: Agricultural economics; Agricultural statistics; Nigeria